Pengaruh Aromaterapi Lavender secara Masase terhadap Tekanan Darah dan Tingkat Stres Mahasiswa Jurusan Keperawatan Poltekkes Palangka Raya - Reny Sulistyowati; Syam’ani Syam’ani (Jurnal Surya Medika (JSM), 2020)
Stress is an individual's adaptive response to various external pressures or demands and produces a variety of disorders including physical, emotional and behavioral disorders. Final year students often experience feelings of stress so that it can interfere with concentration to attend lectures and can even hamper completing education in a timely manner. There are several ways of managing stress, one of which is using aromatherapy. Aromatherapy is a non-pharmacological therapy, which is a type of therapy that applies direct body contact and has a therapeutic effect that combines physiological effects, caused by massage on the body, with psychological effects, which are derived from essential oils. The general purpose of the study is to analyze the effect of aromatherapy on blood pressure and stress levels by using the Kessler Psychological Distress Scale in final semester students. The research method used a quasi-experimental design with a pretest-posttest control group design approach, in 28 intervention groups, namely respondents who were given lavender aromatherapy massage and 28 respondents in the control group. The univariate analysis was conducted to show frequency distribution and bivariate analysis was conducted by independent sample T-test and dependent sample T-test. The results showed that there were significant differences in systolic blood pressure before and after the intervention in the intervention and the control group with a p-value of 0.01 < 0.05. Whereas the stress level variable found that there is no difference in stress levels in the intervention and the control group before and after the intervention with p-value 0.169> 0.05.